Media Tracking Jabar Saber Hoaks sebagai Upaya Mengendalikan Hoaks - Annisa Permata Sari; Neni Yulianita (Bandung Conference Series: Public Relations, 2023)
Abstract. The rapid development of technology and the rapid growth of internet users, especially social media in Indonesia, has made hoax information more easily spread. The spread of hoaxes will harm society and the country, the impact will be chaos in the government and the process of developing the country will be difficult. So that the government requires action in the form of controlling and monitoring existing hoaxes. This research will discuss "Media Tracking Jabar Saber Hoaks as an Effort to Control Hoaxes (Case Study on Social Media of the Government of West Java Province). The purpose of this research is to find out media tracking activities carried out by Jabar Saber Hoaks and the West Java Provincial Government in monitoring the spread of hoaxes on social media Twitter and the West Java Provincial Government's anticipation of hoaxes.The method used in this study is a qualitative method, with a case study approach.The subjects in this study included two key informants and one supporting informant from Jabar Saber Hoaks.Data collection techniques used are in-depth interviews, observation, documentation and literature study. Data analysis techniques are data reduction, data presentation and making conclusions. The results of this study are that the spread of hoaxes on social media Twitter is not much different from other social media. The spread is accompanied by modified images or manipulated, then added with provocative narratives. Media tracking is used by Jabar Saber Hoaks in hoax monitoring activities, but not as the main system. The anticipation that was carried out by the Provincial Government of West Java and Jabar Saber Hoaks in hoaxes was by clarifying and educating them which were distributed through social media and the official Jabar Saber Hoaks website Abstrak.Pesatnya perkembangan teknologi dan pesatnya pengguna internet khususnya media sosial di Indonesia saat ini membuat informasi hoaks menjadi semakin mudah tersebar. Penyebaran hoaks akan merugikan masyarakat maupun negara, dampaknya akan terjadi kekacauan dalam pemerintahan dan proses pembangunan negara akan sulit dilakukan. Sehingga pemerintah memerlukan tindakan berupa pengendalian dan pemantauan terhadap hoaks yang ada. Dalam penelitian ini akan dibahas “Media Tracking Jabar Saber Hoaks Sebagai Upaya Mengendalikan Hoaks (Studi Kasus di Media Sosial Pemerintah Provinsi Jawa Barat”. Tujuan dari penelitian ini adalah untuk mengetahui kegiatan media tracking yang dilakukan oleh Jabar Saber Hoaks dan Pemerintah Provinsi Jawa Barat dalam memantau penyebaran hoaks di media sosial Twitter serta antisipasi Pemerintah Provinsi Jawa Barat terhadap hoaks. Metode yang digunakan dalam penelitian ini adalah metode kualitatif, dengan pendekatan studi kasus. Subjek dalam penelitian ini meliputi dua informan kunci dan satu informan pendukung dari Jabar Saber Hoaks. Teknik pengumpulan data yang digunakan adalah wawancara mendalam, observasi, dokumentasi dan studi kepustakaan. Teknik analisis data yaitu reduksi data, penyajian data dan membuat kesimpulan. Hasil penelitian ini adalah penyebaran hoaks di media sosial Twitter tidak jauh berbeda dengan media sosial lainnya. Penyebarannya disertai gambar yang sudah dimodifikasi atau dimanipulasi, kemudian ditambah dengan narasi-narasi yang provokatif. Media tracking digunakan oleh Jabar Saber Hoaks dalam kegiatan pemantauan hoaks, namun bukan sebagai sistem utama. Antisipasi yang dilakukan oleh Pemerintah Provinsi Jawa Barat dan Jabar Saber Hoaks dalam hoaks adalah dengan melakukan klarifikasi dan edukasi yang disebarkan melalui media sosial dan laman resmi Jabar Saber hoaks.